Der Pirat: d. Drogenkarriere des Jan C. - Aust, Stefan (Hoffmann und Campe, 1990)
Stefan Aust: "Der Pirat". Die Drogenkarriere des Jan C. Verlag Hoffmann und Campe, Hamburg 1990. 351 S., geb., 39,80 DM